Characterization of Empty Adenovirus Particles Assembled in the Absence of a Functional Adenovirus IVa2 Protein - Ostapchuk, Philomena (American Society for Microbiology, 2011)
The molecular mechanism for packaging of the adenovirus (Ad) genome into the capsid is likely similar to that of DNA bacteriophages and herpesviruses—the insertion of viral DNA through a portal structure into a preformed prohead driven by an ATP-hydrolyzing molecular machine. It is speculated that the IVa2 protein of adenovirus is the ATPase providing the power stroke of the packaging machinery. Purified IVa2 binds ATP in vitro and, along with a second Ad protein, the L4 22-kilodalton protein (L4-22K), binds specifically to sequences in the Ad genome that are essential for packaging. The efficiency of binding of these proteins in vitro was correlated with the efficiency of packaging in vivo. By utilizing a virus unable to express IVa2, pm8002, it was reported that IVa2 plays a role in assembly of the empty virion. We wanted to address the question of whether the ATP binding, and hence the putative ATPase activity, of IVa2 was required for its role in virus assembly. Our results show that ATPase activity was not required for the assembly of empty virus particles. In addition, we present evidence that particles were assembled in the absence of IVa2 by using two viruses null for IVa2—a deletion mutant virus, ΔIVa2, and the previously described mutant virus, pm8002. Empty virus particles produced by these IVa2 mutant viruses did not contain detectable viral DNA. We conclude that the major role of IVa2 is in viral DNA packaging. A characterization of the empty particles obtained from the IVa2 mutant viruses compared to wild-type empty particles is presented.